Analysis of Erosion Hazard at Gagakan Sub-Watershed, Blora District, Central Java Province, Indonesia - Auliyani, Diah; Basuki, Tyas Mutiara (Proceeding International Conference on Science and Engineering, 2017)
Availability of soil erosion data is crucial for recovering carrying capacity of a degraded watershed. This study aims to analyze the level of soil erosion hazard in Gagakan Sub-Watershed, located at the downstream of Solo Watershed. Slope steepness of this area vary from very steep at the upper part and flat at the downstream. The dominant land cover is teak forest which consists of young and old stands. The level of soil erosion hazard was calculated by USLE (Universal Soil Loss Equation) and then analyzed spatially using GIS (Geographic Information System). The degree of erosion hazard was classified into five classes, i.e very slight, slight, moderate, severe, and very severe. The results showed that erosion hazard level of Gagakan sub-watershed ranged from very slight to very severe. The dominant is very slight (69%), while the others classified as slight (11%), moderate (15%), severe (1%), and very severe (4%). The countermeasures of soil erosion should be focused on the area with severe and very severe level of erosion hazard.